2021
DOI: 10.1002/cjp2.222
|View full text |Cite
|
Sign up to set email alerts
|

Colonic epithelial cathelicidin (LL‐37) expression intensity is associated with progression of colorectal cancer and presence of CD8+ T cell infiltrate

Abstract: Colorectal cancer (CRC) remains a leading cause of cancer mortality. Here, we define the colonic epithelial expression of cathelicidin (LL‐37) in CRC. Cathelicidin exerts pleotropic effects including anti‐microbial and immunoregulatory functions. Genetic knockout of cathelicidin led to increased size and number of colorectal tumours in the azoxymethane‐induced murine model of CRC. We aimed to translate this to human disease. The expression of LL‐37 in a large (n = 650) fully characterised cohort of treatment‐n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…FFPE tissue cores from 650 CRCs and 50 matched normal pairs were presented within a previously validated TMA [ 13 , 14 , 15 ]. Tissue cores were obtained from chemotherapy and radiotherapy-naïve patients undergoing elective surgery for primary CRC between 1994 and 2009 at Aberdeen Royal Infirmary, Scotland UK.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…FFPE tissue cores from 650 CRCs and 50 matched normal pairs were presented within a previously validated TMA [ 13 , 14 , 15 ]. Tissue cores were obtained from chemotherapy and radiotherapy-naïve patients undergoing elective surgery for primary CRC between 1994 and 2009 at Aberdeen Royal Infirmary, Scotland UK.…”
Section: Methodsmentioning
confidence: 99%
“…These epithelial and immune cell markers were chosen because of previously established biology between them and HMGB1 or cancer [ 13 , 16 ]. Immunohistochemistry was performed using a Dako Autostainer (Dako, Ely, UK), as previously described [ 14 , 15 , 16 ]. Antigen retrieval was performed in 10 mM citrate (pH6) or EDTA (pH 7.8) buffer for 20 min, primary antibody was applied for 60 min, and EnVision+ ™ peroxidase-linked biotin-free synthesis (Dako, Ely, UK) with 3′-3′-diaminobenzidine as chromogen was used for detection.…”
Section: Methodsmentioning
confidence: 99%
“…A human colon-derived epithelial organoid model was established as we previously described [10] from a published protocol [11]. Human colonic mucosa was chelated in 2.5 mM EDTA buffer on ice for 40 min with gentle agitation, then passed through a 100 µM cell strainer.…”
Section: D Organoid Culturementioning
confidence: 99%
“…In addition, via activating TRPV2 and PI3/Akt signaling, and then inducing recruitment of TRPV2 from intracellular vesicles to the plasma membrane of pseudopodia, LL-37 promotes proliferation and growth of breast cancer cells ( Farabaugh et al, 2016 ). On the contrary, it has also been shown that LL-37 can exert anticancer effects on other cancers, including colon cancer, glioblastoma, hematologic malignancy, gastric cancer, and oral squamous cell carcinoma ( Aarbiou et al, 2006 ; Wu et al, 2010b ; Bruns et al, 2015 ; Prevete et al, 2015 ; Chen et al, 2020 ; Porter et al, 2021 ; Chernov et al, 2022 ). There is no smoking gun to explain the reported opposite effects on different cancer types.…”
Section: How Ll-37 Can Eradicate/affect Cancer?mentioning
confidence: 99%